1999
DOI: 10.1038/8816
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of neoplastic cell lineages in Barrett oesophagus

Abstract: It has been hypothesized that neoplastic progression develops as a consequence of an acquired genetic instability and the subsequent evolution of clonal populations with accumulated genetic errors. Accordingly, human cancers and some premalignant lesions contain multiple genetic abnormalities not present in the normal tissues from which the neoplasms arose. Barrett oesophagus (BE) is a premalignant condition which predisposes to oesophageal adenocarcinoma (EA) that can be biopsied prospectively over time becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
299
1
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(335 citation statements)
references
References 18 publications
28
299
1
7
Order By: Relevance
“…Existing evidence shows that p73 plays a role in the regulation of the cell cycle, apoptosis and possibly control of differentiation (Jost et al, 1997;Kaghad et al, 1997;DeLaurenzi et al, 1998;Zhu et al, 1998;Gong et al, 1999), all of which are critical in the oncogenic process. These existing data suggest that p73 activity may be capable of compensating, to some extent, for the early loss of p53 function (through mutation) observed in pre-cancerous oesophageal lesions (Barrett et al, 1999). Indeed, supporting this hypothesis, is the observation that increased expression of p73 was found in oesophageal squamous cancers compared to matched normal tissues; moreover, increased p73 expression significantly correlated with the presence of a p53 defect (Cai et al, 2000).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Existing evidence shows that p73 plays a role in the regulation of the cell cycle, apoptosis and possibly control of differentiation (Jost et al, 1997;Kaghad et al, 1997;DeLaurenzi et al, 1998;Zhu et al, 1998;Gong et al, 1999), all of which are critical in the oncogenic process. These existing data suggest that p73 activity may be capable of compensating, to some extent, for the early loss of p53 function (through mutation) observed in pre-cancerous oesophageal lesions (Barrett et al, 1999). Indeed, supporting this hypothesis, is the observation that increased expression of p73 was found in oesophageal squamous cancers compared to matched normal tissues; moreover, increased p73 expression significantly correlated with the presence of a p53 defect (Cai et al, 2000).…”
Section: Discussionmentioning
confidence: 76%
“…In contrast with other tumour types, p53 mutation is an early event in oesophageal carcinogenesis (Montesano et al, 1996;Barrett et al, 1999). P53 is a critical regulator of the cell cycle (Levine, 1997) and p73 shares significant functional homology with p53 (Kaghad et al, 1997;Zhu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, individual members of genophenotypic clusters of abnormalities have occurred in preferred sequences in relation to other members of the cluster (10) and often have emerged preferentially in early or late histopathologic stages of disease (7,10 -12). In studies of patients with Barrett's esophagus, p53 abnormalities appeared early, in predysplastic diploid cells; during the course of evolution from the premalignant state to invasive disease, tumors with p53 abnormalities progressed through an intermediate stage of tetraploidy (13) to gross aneuploidy (14,15). A similar sequence of events was reported in individual human colon cancers (16,17).…”
mentioning
confidence: 56%
“…Complete loss of wild-type p53 protein within a cell rarely occurs as a result of homozygous deletions or a double mutation, the second allele is usually inactivated by an alternate mechanism to the first. When Barrett's metaplastic tissue was examined, it was found that 95 -100% of cases with 17p LOH also had p53 gene mutations (Gleeson et al, 1998;Barrett et al, 1999), while patients without LOH of the gene still carried a mutated p53 allele (Dolan et al, 1999). This suggests a mutation in one allele of the p53 gene probably occurs first followed by allelic loss of the second during neoplastic progression, resulting in a p53 null phenotype that can promote tumorigenesis in Barrett's oesophagus.…”
Section: Revised 25 June 2003; Accepted 28 July 2003mentioning
confidence: 99%